2006
DOI: 10.1002/yea.1403
|View full text |Cite
|
Sign up to set email alerts
|

Homologous chromosome pairing in Schizosaccharomyces pombe

Abstract: Homologous chromosome pairing is a central feature of meiosis I, contributing to the correct segregation of chromosomes during meiosis. The fission yeast, Schizosaccharomyces pombe, has been widely used to study meiotic chromosome dynamics, partly because studies in this yeast are simplified due to the lack of postpairing synaptic structures. Chromosome pairing in Sz. pombe occurs differentially throughout the genome. Telomeres cluster at the spindle pole body (SPB) at the onset of meiosis, imposing a spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 89 publications
2
19
0
1
Order By: Relevance
“…2B and C). Our observation of polyploidy is consistent with previously described roles for dynein in mitotic cell division across taxa (16,25,37,42,58), while the observation of unpaired diakinetic chromosomes extends those of previous studies that have demonstrated a role for dynein in mediating homologous chromosome pairing in fission yeast (12,60,61). At first glance, these findings appear paradoxical because the germ line tumors in the glp-1 gain-offunction background require additional mitotic divisions.…”
Section: Dlc-1 Inhibits Germ Cell Proliferative Fatesupporting
confidence: 52%
“…2B and C). Our observation of polyploidy is consistent with previously described roles for dynein in mitotic cell division across taxa (16,25,37,42,58), while the observation of unpaired diakinetic chromosomes extends those of previous studies that have demonstrated a role for dynein in mediating homologous chromosome pairing in fission yeast (12,60,61). At first glance, these findings appear paradoxical because the germ line tumors in the glp-1 gain-offunction background require additional mitotic divisions.…”
Section: Dlc-1 Inhibits Germ Cell Proliferative Fatesupporting
confidence: 52%
“…However, the exact role of these structures remains unclear (Loidl 2006;Wells et al 2006). Whether or not recombination can occur outside the context of LinEs has developed into a central question.…”
Section: Discussionmentioning
confidence: 99%
“…concomitant with SC formation and thus well into the recombination process, when stable strand exchange intermediates are already formed between homologous interacting DNAs [7, 21-23]. Additionally, in both fission yeast and budding yeast, mutations conferring disruption of telomere motion have only relatively modest effects on either recombination or pairing [24, 25, 46, 54]. Finally, in the three organisms studied, the movements of mid-prophase chromosomes have a back-and-forth character (rotationally within rat spermatocytes nuclei, longitudinally in S. pombe , and circum-nuclear in S. cerevisiae ), which does not have the effect of ‘stirring’ chromosomes (Figure 1).…”
Section: Role(s) Of Chromosome Motion For Mid-prophase Of Meiosismentioning
confidence: 99%